The Limits of Administrative Authority to Withdraw Defective Administrative Decisions in Modern National and Comparative Legislation - Ahbaini Ashour, Assist. Lect. Anwar (Basra studies journal, 2026)
This study examines the limits of the public administration’s authority to withdraw defective administrative decisions in light of modern national legislation and comparative legal systems. The significance of this topic arises from the interaction between two opposing principles: the principle of legality, which requires the elimination of unlawful administrative acts, and the principle of legal certainty, which demands the protection of legitimate expectations and the stability of acquired legal situations. The study clarifies the concept of administrative withdrawal and distinguishes it from related legal concepts, particularly administrative revocation, which operates only for the future, and judicial annulment exercised by administrative courts. It also examines the legal basis of this authority, emphasizing that it is not an absolute prerogative of the administration but a legal mechanism aimed at correcting unlawful administrative acts, provided that it does not undermine legal stability in administrative relations. Methodologically, the study adopts a comparative analytical approach by examining legislative texts and judicial rulings in Iraq, Egypt, France, and Jordan. The research is structured into three main sections. The first addresses the conceptual framework and legal basis of withdrawal. The second focuses on its substantive, temporal, and procedural limitations, with a distinction between rights-creating and non-rights-creating decisions, as well as between substantial and minor defects, in addition to exceptions such as fraud, deception, and null administrative acts. The third section discusses practical applications and contemporary comparative trends, offering a critical assessment of the national legislative framework.